Synthesis and Crystal Structure of a Novel Hexahomotrioxacalix[3]cryptand - Jiang, Xue-Kai; Deng, Min; Mu, Lan; Zeng, Xi; Zhang, Jian-Xin; Yamato, Takehiko (Asian Journal of Chemistry, 2012)
A novel hexahomotrioxaacalix[3]cryptand was synthesized and its crystal structure has been determined. The crystals obtained by recrystallization from ethanol, are singal clinic, space group is C2/c, a = 19.6831(16)Å, b = 16.8180(16)Å. c = 29.267(3)Å, a = 90.00º, b = 105.222(4)º, g = 90.00º. 1H NMR spectroscopy and X-ray single-crystal structure results suggested that this compound was fixed in a cone conformation.